Research of non-equilibrium dynamic of pasture ecosystems in Mongolia - Chimedregzen, Davaasuren; Togtokh, Chuluun; Myagmarsuren, Altanbagana (Journal of Applied Science and Engineering A, 2024)
Wiens, DeAngelis and Waterhouse, and Ellis and Swift first introduced the concept of non-equilibrium rangelands. In 1988, Ellis and Swift further proposed that rainfall variability could degrade rangeland ecosystems, with non-equilibrium conditions arising when the rainfall coefficient of variation surpasses 33%. It means that rangeland’s dynamics, particularly livestock dynamics, are governed by frequent droughts. Direct application of this statement in Mongolia shows that the drylands of Mongolia with annual precipitation of less than 175 mm exhibit non-equilibrium dynamics. These areas include the Gobi and the southern part of the dry steppe. Based on the above theoretical basis and research, the precipitation coefficient of variability in Mongolia was re-mapped using data from a total of 68 stations. Otherwise, for the above stations the analysis was done using 58 year time series, and the above stations were generated by creating a geographical distribution. One of the goals of this work was to show the results of coefficient of variation for natural zones. From the resulting map, shows an expanding area with a precipitation coefficient of variability exceeding 33%, and in terms of natural zones, a greater spread is observed towards the steppe region. This indicates that the area of ​​unbalanced pasture ecosystems is expanding, and it shows the need for alternative management solutions at the level of livestock sector and pasture utilization in the region. Another important point is that global warming, livestock numbers, and pasture overcapacity are significantly affecting the imbalance in the above-mentioned pasture ecosystem, so further comprehensive studies are needed.